Cast a Ballot or Protest in the Street - Did our Grandparents Do More of Both? An Age-Period-Cohort Analysis in Political Participation - Boarini, Romina (OECD Statistics Working Papers, 2015)
Recent research suggests that younger generations are less likely to be engaged in formal political participation than older ones. However, there is little evidence on the trends for non-formal participation (e.g. signing petitions, demonstrations, etc.) This paper tries to fill a gap in this field by looking at the evolution of extra-parliamentary participation in politics through various measures of civic and political engagement, based on data from six waves of the European Social Survey. The paper confirms that younger generations in European countries participate less in politics through formal activities. A similar trend is observed for extra-parliamentary participation, although this trend is less clear-cut. The results also show that the financial crisis of 2007-2009 witnessed a halt in the downward trend of period effects in the various forms of political participation, followed by the increase of period effects on both formal and extra-parliamentary political participation in the subsequent years (2011-2012.)